The effect of increased manufacturing rate on risk of low back pain - Ahmadi, Saeid; Zare, Sajad; Ghanbari, Reza; Bahrami, Sahar; Zaroushani, Vida (Archives of Advances in Biosciences, 2018)
The blood bank unit is one of the most important and fundamental units in every hospital especially in emergency situations. Lack of access to medical records related to individual’s blood transfusion can postpone blood transfusion when it is essentially needed which can in turn increase patients' risks. Meanwhile, the role of a blood bank information system is crucial in accessing this information, thereby improving the quality of available care. This research was conducted to determine the status of the blood bank information system of the hospitals affiliated to Shahid Beheshti University of Medical Sciences.This descriptive- practical study investigated the blood bank information systems of 11 hospitals affiliated to Shahid Beheshti University of Medical Sciences in 2015. Data collection was performed through observation and interview, using a checklist and questionnaire. The validity of the instrument was determined through content validity and its reliability was confirmed through retesting. Data analysis was conducted using descriptive statistics.All blood bank information systems under investigation were semi-mechanized. It was impossible to send the full reports electronically and to present dynamic reports. The blood bank staff were not aware of the existence and significance of the relevant standards and no specific blood bank software were used.Mechanized blood bank information systems bring about effective communication in various health care organizations. They lead to the application of relevant novel technologies while increasing patients’ safety and satisfaction.